Dynamics of the Properties of Oat and Buckwheat Grains in the Growth Technology - A. M. Ourbantchik; V. A. Sharshunou; M. M. Haldova; L. V. Shustava (Алматы технологиялық университетінің хабаршысы, 2022)
Сurrently, a large number of publications and studies are aimed at the development of functional, enriched and biologically active food products. Rational use of grain resources is the basis for the development of all branches of agriculture and many branches of the agro-industrial complex. The paper studies the technological properties of oat and buckwheat grains as raw materials for the production of biologically active products. Grain of oats and buckwheat has high values of seed properties – germination energy (80 ± 5) %, (70 ± 5) % and germination (86 ± 6) %, (64 ± 4) %, respectively, and can be used in the technology of obtaining biologically active plant raw materials. Analytical dependences of changes in the physico-chemical properties of oat and buckwheat grains during germination have been obtained, which make it possible to predict changes occurring with grain in the range from 1 h to 35 h of germination. The results obtained indicate the prospects of using oat and buckwheat grains for the production of biologically active raw materials, and commercialization of the results obtained on an industrial scale.